Contribuição ao estudo do Método físico-químico de dosagem do solo-cimento - Rodrigues, Maria da Glória Marcondes (1992)
This dissertation concerns a study developed on the method known as Physico-chemical Assessment of Soil-Cement, by using four soils of lateritic weathering with different characteristics. The method's precision was appraised by means of repeatability and reproducibility indicators. For this purpose, ten assays were made on each soil with the same oparator and an interlaboratorial program using four different laboratories, the four soils and three repetitions per sample. The influences exerted by an admixture (CaCl2), ultrasonic pretreatment and temperature on the method's results were also observed. This thesis further presents a few correlations between percent volumetric change and soil characteristics. Finally, a new criterion is defined to select the cement content required by the soil.